Penciptaan Film Animasi “Afeksi” Dengan Teknik Digital 2 Dimensi Melalui Pendekatan Surealis - Nur Afif; Arif Sulistiyono; Pandan Pareanom Purwacandra (Journal of Animation and Games Studies, 2017)
Affection is the Indonesian language of a scientific dictionary which means affection. The affection that is raised in this animated film is the affection between mother and a son who grew up. Conflict and emotion between the two are present when the child goes to maturity, emotional instability as a teenager in the face of various philosophies and the reality of life. This is what makes the distance and time separator, until regret, loneliness and longing that leads back to the mother.The creation of the animated film is presented in the form of 2D animation with hardlight lighting techniques without the use of narration and dialogue. As a supporter built music in such a way that can strengthen the suasasa in every groove.Visualization of the film deliberately carry the concept of contemporary theatrical dance where in terms of content and motion is still insert elements of culture. Not to mention the surreal approach is also applied in this work. The addition of water element as a form of emphasis on expression and emotion as well as to add an artistic impression as a visual support.Keywords: affection, 2D animation, surealis, teatrichalAbstrak Afeksi merupakan bahasa Indonesia dari kamus ilmiah yang berarti kasih sayang. Kasih sayang yang diangkat dalam film animasi ini adalah kasih sayang antara ibu dan seorang putra yang dibesarkannya. Konflik dan emosional diantara keduanya hadir kala si anak menuju kedewasaan, ketidakstabilan emosi saat remaja dalam menghadapi berbagai filosofi dan realitas kehidupan. Hal inilah yang menjadikan pemisah jarak dan waktu, hingga sesal, sepi dan rindu yang menuntunnya kembali kepada sang ibu.Penciptaan film animasi ini disajikan dalam bentuk animasi 2D dengan teknik pencahayaan hardlight tanpa menggunakan narasi dan dialog. Sebagai penunjangnya dibangunlah musik sedemikian rupa sehingga dapat memperkuat suasasa dalam setiap alurnya.Visualisasi film sengaja mengusung konsep tarian teatrikal kontemporer dimana dari segi konten maupun gerak masih menyisipkan unsur budaya. Tidak lupa pendekatan surealis juga diterapkan dalam karya ini. Penambahan elemen air sebagai wujud penekanan ekspresi dan emosional sekaligus untuk menambahkan kesan artistik sebagai penunjang visualisasi. Kata kunci: afeksi, animasi 2D, surealis, teatrikal